The Benefits of a Jeffersonian Transcript - Park, Song Hee; Hepburn, Alexa (Frontiers in Communication, 2022)
Over the past six decades, researchers in conversation analysis have repeatedly shown that everyday social activities such as inviting a friend over, interviewing a police suspect, teaching a class, or cross-questioning in a courtroom - are achieved in orderly and reproducible ways. Jeffersonian transcription has been refined to both capture and crystallize the interactionally relevant specifics of how such tasks get done. Conversation analytic work has shown that by leaving out features like the timing of turns, and changes in prosody, volume and other vocal and embodied specifics of delivery, a standard orthographic transcript bleaches out crucial components of how humans perform discursive actions, and how they continuously analyze one another across sequences of talk. This short paper will overview some of the benefits of investing time in the Jeffersonian system. Rather than simply describing the system, we will illustrate the analytic usefulness of its systematic and detailed transcription practices; we show how transcription facilitates a clearer picture of how things get done in interaction.